Relationship between Family Support and Toddler Basic Immunization Completeness During the COVID-19 Pandemic - Susiana; Lukman Nulhakim; Tini (PT FORMOSA CENDEKIA GLOBAL, 2023)
The implementation of health protocols during the COVID-19 pandemic has had an impact on toddler health services, especially in reducing immunization coverage. The impact is that there will be a PD3I disaster beyond the COVID-19 pandemic in the future. Family support aims to create optimal family health status. The purpose of this study was to determine the relationship between family support and the completeness of basic immunization status for toddlers during the COVID-19 pandemic. This research is a type of correlational quantitative research with a cross sectional design. The research sample consisted of 91 mothers with toddlers taken by purposive sampling in the working area of the UPT Puskesmas Tubaan. Data were analyzed using the Chi Square Test with a significance level of 0.05